Antimicrobial peptides: Promising alternatives in the post feeding antibiotic era. Issue 3 (24th October 2018) - Wang, Jiajun; Dou, Xiujing; Song, Jing; Lyu, Yinfeng; Zhu, Xin; Xu, Lin; Li, Weizhong; Shan, Anshan
Abstract: Antimicrobial peptides (AMPs), critical components of the innate immune system, are widely distributed throughout the animal and plant kingdoms. They can protect against a broad array of infection‐causing agents, such as bacteria, fungi, parasites, viruses, and tumor cells, and also exhibit immunomodulatory activity. AMPs exert antimicrobial activities primarily through mechanisms involving membrane disruption, so they have a lower likelihood of inducing drug resistance. Extensive studies on the structure‐activity relationship have revealed that net charge, hydrophobicity, and amphipathicity are the most important physicochemical and structural determinants endowing AMPs with antimicrobial potency and cell selectivity. This review summarizes the recent advances in AMPs development with respect to characteristics, structure‐activity relationships, functions, antimicrobial mechanisms, expression regulation, and applications in food, medicine, and animals. Abstract : This review systematically summarizes the recent advances in AMPs development with respect to characteristics, structure‐activity relationships, functions, antimicrobial mechanisms, expression regulation, and applications in food, medicine, and animals. The developments of peptidomimetics and AMPs/peptidomimetics‐antibiotics hybrids as the next generation of antimicrobial agents are also introduced. The broad‐spectrum antimicrobial activity and nonspecific physical membrane disruption mechanism of AMPs highlight their potential to be developed as potential alternatives to antibiotics.